OVERCOMING CHALLENGES IN IMPLEMENTING MODERN METHODOLOGY IN FOREIGN LANGUAGE TEACHING - Maxmudxo’jayeva Nasibaxon Azim qizi; Barno Ziyatova (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article explores the major challenges faced when implementing modern methodologies in foreign language teaching and proposes practical solutions supported by international research. It discusses problems such as the persistence of outdated methods, insufficient teacher training, inadequate technological resources, low learner motivation, and institutional constraints. Drawing on recent studies, the paper argues that overcoming these barriers requires a comprehensive approach involving curriculum reform, teacher professional development, technological investment, motivational strategies, and institutional support. These measures are essential for aligning foreign language education with global communicative needs.